Pentingnya Nilai Tanggung Jawab Pemuda Dalam Kehidupan Gereja Paroki Hati Kudus Yesus di Rantau Pulut - Adeen Basil; Rose Eve Abillene (Journal New Light, 2023)
The background to writing this thesis was complaints from priests, catechists, and the young generation themselves (OMK) about the lack of knowledge and understanding of the younger generation regarding the value of the responsibilities they carry. The aim of writing this thesis is to help the young generation of Catholics (OMK) understand their duties and responsibilities as members of the Church. Apart from that, this research also aims to help pastors understand and recognize the problems faced by young people. In analyzing the problem, the author uses qualitative research with a phenomenological approach. By using this phenomenological approach, the author tries to analyze and interpret the personal experiences of the informants regarding the importance of the value of youth responsibility in the life of the Rantau Pulut Sacred Heart of Jesus Parish church. Data collection in this research used observation, interview and note-taking techniques. In this research, the author found that the majority of young Catholics in the Rantau Pulut Parish have not fully participated in the life of the Church. This is due to a lack of motivation and encouragement from parents and pastors. As the spearhead of youth mobilization, pastoral workers are an important element in support and guidance so that young people are encouraged to participate in Church activities.